Economic Integration across Latin America : Evidence from Labor Markets, 1990-2013 - Lederman, Daniel; Robertson, Raymond (World Bank, Washington, DC, 2016)
Combining macroeconomic and microeconomic data and three indicators of international market integration, this paper assesses the degree to which Latin American labor markets are integrated. The results suggest that relative to East Asia, Latin American labor markets are somewhat more integrated, but considerable differences across countries persist. In addition, the evidence indicates that the degree of labor market integration across Latin American borders is significantly less than that of labor markets within Mexico and within the United States in two of the three indicators. These differences may suggest opportunities for efficiency gains from further labor market integration.